Child development in rural areas children as from the baseline study of the National Program Cuna Más, 2014 - Tarazona C., David (2016)
Objectives. To know the levels of child development and explore its relationship with socioeconomic status and maternal education. Methods. Quantitative – exploratory study done between March and August 2013. The study include information about 5859 children of 1- 24 months at the interview and their 5723 mothers (or primary caregiver), from 5620 rural homes. We applied an adapted version of Age and Stages Questionnaire ASQ-3 and a socio-demographic questionnaire. Results. Scores in the scales of communication and fine motor showed that, as age is higher, the gap in the results of the scales increases. In general, children less poor quartile in the sample obtain higher scores than children from the poorest to the five dimensions evaluated quartile. On the other hand, there are differences in the five scales and the total score between the scores achieved by children with mothers more and less educated. Conclusions. The study has established that there are differences in the scores obtained in the ASQ-3 based in variables as age, maternal education and wealth level.